Local Ultrasonic Hyperthermia and Thermo-ablation: A Description and Theoretical Evaluation of Two Alternative Concepts for the Heat Therapy of Tumours - Lierke, Ernst-Günter; Hemsel, Tobias (Acta Acustica united with Acustica)
Ultrasonic hyperthermia and thermo-ablation are two promising alternatives for local overheating of deep-seated human tumours. After a short characterisation of the two techniques and the identification of the main parameters, results of an analytical theory of local heat up, cooling, and heat diffusion are presented. The theory is based on a spherical model for hyperthermia with a critical thermal dose and on a cylinder-symmetrical model for thermo-ablation with a critical temperature threshold for thermal toxicity and cell death through coagulative necrosis. Two representative hard ware concepts are discussed. The hyperthermia applicator consists of a MHz transducer, which rotates concentrically in a water filled capsule with acoustically transparent window, and radiates collimated or focussed ultrasound under 45$\,^{°}$ into a concentric target area of nearly spherical symmetry. The applicator for thermo-ablation is a MHz transducer which radiates high intensity focussed ultrasound (HIFU) into "cigar shaped" target areas at the focal zone. Typical therapy diagrams for both techniques are presented. They show therapeutic target volumes as functions of the therapy time with the peak temperature or the radiated acoustic power as parameters. These diagrams are discussed under consideration of power requirement, maximal sound intensity, and power efficiency at close to optimized frequency conditions.

Verlässlichkeitorientierte Technologiebewertung innovativer Aktortechnologien am Beispiel von Formgedächtnislegierungen - Müller, Thomas; Schiedeck, Florian; Hemsel, Tobias (2. Tagung des DVM -- Arbeitskreis Zuverlässigkeit mechatronischer und adaptronischer Systeme: Absicherung der Systemzuverlässigkeit, Koblenz)
EN: Although the use of new actuator technologies is quite enthusiastic, the realization of innovative systems based on these principles fails because of doubts in dependability. Until now, new working principles for actuators have not been systematically investigated in the means of dependability. Therefore we developed a proceeding for a dependability-oriented evaluation of technologies. This is shown in the case of shape memory alloy actuators. DE: Die Realisierung von Systemen mittels innovativer Aktortechnologien scheitert oftmals an der Skepsis gegenüber der Verlässlichkeit (Vertrauen in die zuverlässige und sichere Funktionalität der Technologie). Diese liegt darin begründet, dass neue Aktortechnologien bzw. die Integration von innovativen physikalischen Wirkprinzipen innerhalb neuer Aktorkonzepte bisher noch nicht systematisch im Kontext der Verlässlichkeit untersucht werden. Daher haben wir ein Vorgehen zur verlässlichkeitsorientierten Technologiebewertung entwickelt. Neben der detaillierten Darstellung des Vorgehensmodells wird es exemplarisch anhand von Formgedächtnislegierungen zur Entwicklung innovativer Antriebslösungen angewendet.
Keywords: EN: Dependability; Reliability; Evaluation of Technology; Actuators; Shape Memory Alloys DE: Verl{\

Driving concepts for bundled ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias; Sattel, Thomas; Vasiljev, Piotr; Wallaschek, Jörg (Journal of Electroceramics)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable, e.g., to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: The electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well-organized and at last controlled to get an optimized drive that is not oversized and costly.
Keywords: Ultrasonic linear motor; High power; Control; Modeling; Characteristics

The active guidance module of a rail-bound vehicle as an application for the dependability oriented design in self-optimizing systems - Sondermann-Wölke, Christoph; Geisler, Jens; Müler, Thomas; Trächtler, Ansgar; Böcker, Joachim (ASME 2008 -- International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))
Integrating dependability in self-optimizing systems is a challenging task. Self-optimizing systems incorporate on the one hand the opportunity to apply novel solutions to complex mechatronic systems, but on the other hand constitute a possible risk because of non-determined behavior. The dependability concept in this paper covers both aspects: Increasing safety with selfoptimization and minimizing the risk of self-optimization. This dependability concept is combined with the self-optimization process of the active guidance module which is currently under development at the Collaborative Research Center 614 at the University of Paderborn.

Tactile tissue characterisation by piezoelectric systems - Stroop, Ralf; Uribe, David Oliva; Martinez, Melisa Orta; Brökelmann, Michael; Hemsel, Tobias; Wallaschek, Jörg (Journal of Electroceramics)
For devices having non-linear contact, load plays a fundamental role. Variations in the characteristics of the load cause change in eigenfrequency and amplitude of the vibration. In most technical applications, this unwanted behaviour is cancelled by the use of control algorithms. However, multiple applications, like bond quality monitoring or chemical and pressure sensors, have found that the load may be characterised by interpreting the change in characteristics of a resonant vibrating device used as a sensor. Surgical resection of tumours is a very difficult task. After localising the tumour by the use of imaging techniques, the resection demands the surgeon to decide where and what to resect based on visual and tactile differentiation of tumour and healthy tissue. Exactness of this process could be enhanced if we can provide the surgeon with a device capable of evaluating mechanical characteristics of the tissue much more accurately than the surgeon himself can do. As the mechanical characteristics of tumour and healthy tissue differ but slightly, the task is to design a system with high sensitivity. Therefore, we have developed a resonant actuator-sensor that allows the differentiation among distinct media that have similar mechanical characteristics to tumour and healthy tissue using a piezoelectric bimorph. The design is based on the detection and evaluation of frequency shift and amplitude variation of the fundamental and higher harmonics using one layer for the resonant excitation of vibration and the other one as the sensing element.
Keywords: Piezo ceramics; Bimorph; Tactile sensor; Tumour tissue

Fundamental experiments as benchmark problems for modeling ultrasonic micro-impact processes - Twiefel, Jens; Potthast, Christian; Mracek, Maik; Hemsel, Tobias; Sattel, Thomas; Wallaschek, Jörg (Journal of Electroceramics)
Many ultrasonic processes are based on the mechanical contact of oscillating parts. Within ultrasonic machining (drilling, milling, grinding) micro impacts lead to abrasion at the processed workpiece and hopefully do not damage the tool. In ultrasonic motors ideally neither part gets worn. Thus the appropriate design of contact partners as well as their kinematics is a substantial task during the development of such devices. A first step to optimize contact mechanics is to understand their behavior and dependencies on parameter variations, such as vibration amplitude and pre-stress of the impacting parts. For a detailed understanding models validated with convincing experimental data from measurements are absolutely essential. This paper focuses on simple vibro-impact experiments which can be used as benchmark data for future models. The setup of the experiment and first experimental investigations are described in detail.
Keywords: Contact measurements; Vibro-impact; Ultrasonic application

Development of a biomedical tissue differentiation system using piezoelectric actuators - Uribe, David Oliva; Stroop, Ralf; Hemsel, Tobias; Wallaschek, Jörg (Frequency Control Symposium, 2008 IEEE International)
In neurosurgery, delineation of tumor boundaries during resection of brain tumors is of substantial relevance. During operation distinction between tumor and healthy tissue rely on the abilities of the surgeon based on visual and tactile differentiation. In this paper a high sensitivity actuator-sensor system using a piezoelectric bimorph is presented. Frequency shift and transfer function of the bimorphpsilas voltages are detected and evaluated. Sensorpsilas sensitivity is evaluated using two frequency controls strategies: A phase-locked loop (PLL) and a self-oscillating circuit. Results of measurements conducted on gel-phantoms are presented and discussed.
Keywords: biomedical measurement; brain; cancer; neurophysiology; phantoms; phase locked loops; piezoelectric actuators; surgery; tactile sensors; transfer functions; tumours; PLL; biomedical tissue differentiation system; brain tumor resection; frequency control; frequency shift; gel-phantom; high sensitivity actuator-sensor system; neurosurgery; phase-locked loop; piezoelectric actuators; piezoelectric bimorph; self-oscillating circuit; sensor sensitivity; tactile differentiation; tactile sensor system; transfer function; tumor boundary; visual differentiation; Biomedical measurements; Circuits; Frequency control; Neoplasms; Neurosurgery; Phase locked loops; Piezoelectric actuators; Surges; Transfer functions; Voltage

Modellierung der Hysterese- und Adhäsionseffekte zwischen Bremsbelag und Bremsscheibe - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Modelling of Hysteresis and Adhesion Effects between Brake Pad and Disc - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Non-destructive ultrasonic test of orange dehydration - Camarena Gandia, Francisco; Hemsel, Tobias; Espinosa, Victor; Twiefel, Jens; Ardid, Miquel; Martinez-Mora, Joan; Gandia, Joan Babtiste (Proceedings of 19th international congress on Acoustics, Madrid)
Penetration tests (Magness-Taylor, force/deformation, Kramer multiblade shear) applied directly over the peel of the fruit are the most acceptable methods for measuring firmness and turgidity of fruits and vegetables [1, 2]. To replace these destructive and mechanical penetration methods by non-destructive ultrasonic measurements implies a great advance in order to obtain fast studies about the state of the fruit at the time of harvest, during storage, and in the distribution points. Moreover, there are other advantages since this technique can be fast, non-destructive, fully automated, and performed on-line [1]. Within this context, the objective of this study was to examine the relationship between physico-mechanical characteristics (oil-gland break stress, thickness and dehydration) and ultrasonic characteristics in the ``Salustiana'' orange peel during the complete dehydration process of the orange at ambient conditions. After a description of the measurement system [3], the fruit selection procedure and the measurement protocol, we analyze the results of the change of physico-mechanical and ultrasonic properties in the orange peel and their change with storage time.

Schwingungsverhalten elastischer Körper mit nichtlinearen Kopplungen in ausgedehnten Reibkontakten - Genzo, Alexander; Sextro, Walter; Panning, Lars (VDI-Berichte)

Resonant vibrating sensors for tactile tissue differentiation - Hemsel, Tobias; Stroop, Ralf; Oliva Uribe, David; Wallaschek, Jörg (Journal of Sound and Vibration)
Surgical resection of brain tumours is a difficult task. To enhance surgery results, a tactile sensor is wanted that gives better resolution and sensitivity than the human tactile sense. The characteristics of resonant vibrating piezoelectric elements change with varying load. This allows for calculation of mechanical load parameters by measuring electrical quantities. Different setups of piezoelectric sensors have been used to investigate soft materials. Finally, a piezoelectric bimorph sensor gave good results for distinguishing tissue mimicking gel-phantoms with different gelatine concentrations.

Perspectives of Tumour Therapy by Local Ultrasonic Hyperthermia and Thermal Ablation - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 19th international congress on Acoustics, Madrid)

Fundamental Study on A Thickness-Shear Transformer using X-Cut Lithium Niobate - Shigematsu , Takashi; Morita, Takeshi; Hemsel, Tobias (Proceedings of Symposium on Ultrasonic Electronics)

On Nonlinear Forced Vibration of Shrouded Turbine Blades - Szwedowicz, J; Visser, R; Sextro, Walter; Masserey, P. A (Journal of Turbomachinery)
Numerical predictions of the forced vibration of a disk assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disk assembly, numerical static, free, and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a nonlinear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0â30deg) between the circumferential direction and the normal vector to the contact surface.

Design and Construction of a 3D-Scanning-Laservibrometer - Becker, C; Wedman, S; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric transducer design via multiobjective optimization - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
The design of piezoelectric transducers is usually based on single-objective optimization only. In most practical applications of piezoelectric transducers, however, there exist multiple design objectives that often are contradictory to each other by their very nature. It is impossible to find a solution at which each objective function gets its optimal value simultaneously. Our design approach is to first find a set of Pareto-optimal solutions, which can be considered to be best compromises among multiple design objectives. Among these Pareto-optimal solutions, the designer can then select the one solution which he considers to be the best one. In this paper we investigate the optimal design of a Langevin transducer. The design problem is formulated mathematically as a constrained multiobjective optimization problem. The maximum vibration amplitude and the minimum electrical input power are considered as optimization objectives. Design variables involve continuous variables (dimensions of the transducer) and discrete variables (the number of piezoelectric rings and material types). In order to formulate the optimization problem, the behavior of piezoelectric transducers is modeled using the transfer matrix method based on analytical models. Multiobjective evolutionary algorithms are applied in the optimization process and a set of Pareto-optimal designs is calculated. The optimized results are analyzed and the preferred design is determined.
Keywords: Piezoelectric transducer

Multiobjective optimization of piezoelectric transducers using evolutionary algorithms - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Dynamic Behaviour of Elastic Bodies Coupled by Extended Friction Contacts - Genzo, Alexander; Sextro, Walter (Proceedings of ISMA - International conference on noise and vibration engineering)
Keywords: Noise; Vibration engineering

Unsteady rolling contact of rubber wheels - Gutzeit, F; Sextro, Walter; Kröger, Matthias (Analysis and Simulation of Contact Problems)
This paper presents a model for unsteady longitudinal slippage of a loaded rubber wheel. The aim of modelling was to calculate the dynamical contact behavior in a numerical efficient way. Further on, simulation results are compared to experimental data.

Powder coating fabrication by ultrasonic standing wave atomizer - Hemsel, Tobias; Henning, C; Kauczor, Christopher; Littmann, Walter (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Control of Bundled Miniature Ultrasonic Linear Motors - Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric linear motor concepts based on coupling of longitudinal vibrations - Hemsel, Tobias; Mracek, Maik; Twiefel, Jens; Vasiljev, Piotr (Ultrasonics)
Classically, rotary motors with gears and spindle mechanisms are used to achieve translatory motion. In means of miniaturization and weight reduction piezoelectric linear motors are of interest. Several ultrasonic linear motors found in literature base on the use of two different vibration modes. Most often flexural and longitudinal modes are combined to achieve an elliptic micro-motion of surface points. This micro-motion is converted to direct linear (or translatory) motion of a driven slider. To gain high amplitudes of the micro-motion and thus having a powerful motor, the ultrasonic vibrator should be driven near the eigenfrequency of its modes. Additionally, low mechanical and electrical losses lead to increased efficiency and large amplitude magnification in resonance. This demands a geometrical design that fits the eigenfrequencies of the two different modes. A frequency-deviation of only a few percent leads to non-acceptable disturbance of the elliptical motion. Thus, the mechanical design of the vibrators has to be done very carefully. Within this contribution we discuss different motor designs based on the coupling of two the same longitudinal vibrations within one structure to generate an elliptic motion of surface points. Different concepts based on piezoelectric plates and Langevin transducers are compared. Benefits and drawbacks against the combination of longitudinal and bending modes will be discussed. Numerical results of the stator vibration as well as motor characteristics are validated by measurements on different prototypes.
Keywords: Piezoelectric linear motor

Model Based Analysis of Piezoelectric Transformers - Hemsel, Tobias; Priya, S (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model based analysis of piezoelectric transformers - Hemsel, Tobias; Priya, S (Ultrasonics)
Piezoelectric transformers are increasingly getting popular in the electrical devices owing to several advantages such as small size, high efficiency, no electromagnetic noise and non-flammable. In addition to the conventional applications such as ballast for back light inverter in notebook computers, camera flash, and fuel ignition several new applications have emerged such as AC/DC converter, battery charger and automobile lighting. These new applications demand high power density and wide range of voltage gain. Currently, the transformer power density is limited to $40 W/cm{^3}$ obtained at low voltage gain. The purpose of this study was to investigate a transformer design that has the potential of providing higher power density and wider range of voltage gain. The new transformer design utilizes radial mode both at the input and output port and has the unidirectional polarization in the ceramics. This design was found to provide 30 W power with an efficiency of 98% and 30 $\,^{°}$C temperature rise from the room temperature. An electro-mechanical equivalent circuit model was developed to describe the characteristics of the piezoelectric transformer. The model was found to successfully predict the characteristics of the transformer. Excellent matching was found between the computed and experimental results. The results of this study will allow to deterministically design unipoled piezoelectric transformers with specified performance. It is expected that in near future the unipoled transformer will gain significant importance in various electrical components.
Keywords: Piezoelectric transformers

Error-Workspace Analysis of Plane Mechanisms - Hofmeisterro, Adolf; Sextro, Walter; Röschel, Otto (Proceedings of EUCOMES, the first European Conference on Mechanism Science)

Focusing cross-fire applicator for ultrasonic hyperthermia of tumors - Lierke, E.G.; Hemsel, Tobias (Ultrasonics)
An improved concept for ultrasonic hyperthermia of tumors is presented. This concept is based on past experience of a German government supported project [1], which ended in 1984. It offers a low cost alternative to common RF- and microwave methods for hyperthermia of tumors with volumes between 1 and 40 ml at treatment times between 30 and 60 min. Our new version of the system considerably improves the temperature suppression in the healthy tissue around the target area and enables the adjustment of the beam width to the actual tumor size and the field geometry to the depth and shape of the tumor. The applicator can be used for moderate hyperthermia with tissue overheating up to 10 K or for ablation therapy with short high temperature pulses. Its central area is free for the integration of a commercial ultrasonic diagnostic sector scanner or a Doppler flow sensor in order to support the adjustment of the transducer and to monitor the whole area during the therapy.
Keywords: Moderate hyperthermia

Focussing Cross-Fire Applicator for Ultrasonic Hyperthermia of Tumors - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Powder Transport by Ultrasonic Waves - Mracek, B; Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Synergetic driving concepts for bundled miniature ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias (Ultrasonics)
Rotary ultrasonic motors have found broad industrial application in camera lens drives and other systems. Linear ultrasonic motors in contrast have only found limited applications. The main reason for the limited range of application of these very attractive devices seems to be their small force and power range. Attempts to build linear ultrasonic motors for high forces and high power applications have not been truly successful yet. To achieve larger force and higher power, multiple miniaturized motors can be combined. This approach, however, is not as simple as it appears at first glance. The electromechanical behaviour of the individual motors differs slightly due to manufacturing and assembly tolerances. The individual motor characteristics are strongly dependent on the driving parameters (frequency, voltage, temperature, pre-stress, etc.) and the driven load and the collective behaviour of the swarm of motors is not just the linear superposition of the individual drive's forces. Thus, the bundle of motors has to be synchronized and controlled appropriately in order to obtain an optimized drive that is not oversized and costly. We have investigated driving and control strategies of a set of linear ultrasonic motors. Our contribution will be divided into three main parts. In part I ultrasonic linear motors will be introduced. In part II driving strategies for a single motor as well as for a bundle of motors will be presented. These concepts will be verified by simulation results and experimental data. In part III a simplified model for the motor's electromechanical behaviour will be given.
Keywords: Ultrasonic linear motor

Self configuration of a novel miniature ultrasonic linear motor - Mracek, Maik; Vasiljev, Piotr; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Model based design of piezoelectric generators utilizing geometrical and material properties - Richter, Björn; Twiefel, Jens; Hemsel, Tobias; Wallaschek, Jörg (ASME 2006 International Mechanical Engineering Congress and Exposition)
This paper presents a general model based on the electromechanical circuit theory. The model is set up as a mechanical equivalent model for base excited systems and describes the behaviour of a piezoelectric element around one resonance frequency which is sufficient for most practical applications. The model is extended to obtain the influence of geometrical and material properties. The derivated properties are used to describe the parameters of the general model which is easy to handle. Using this model either the calculation of the output power on a specific electric load or the determination of the design of the used piezoelectric element for a needed electric output power is possible. The paper focuses on the design of the ratio of length and width of a piezoelectric bimorph. The validity of the model is shown by the comparison of computed and experimental results.
Keywords: Materials properties; Design; Generators

Comparison of Piezoelectric and Shape Memory Alloy Based Actuators - Schiedeck, Florian; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

The use of shape memory alloy wires in actuators - Schiedeck, Florian; Hemsel, Tobias; Wallaschek, Jörg (Solid State Phenomena)

Contact behaviour of a sliding rubber element - Sextro, Walter; Moldenhauer, Patrick; Wangenheim, M; Lindner, Markus; Kröger, Matthias (Analysis and Simulation of Contact Problems)
Friction occurs in the contact between tyre and road. The friction of rubber material on dry surfaces is dominated by hysteresis and adhesion effects. Hysterisis friction is characterised by the energy dissipation within the visco-elastic material, which is caused by its deformation while passing the surface roughness. Hysteresis effects are modelled by an extended linear visco-elastic material with several Maxwell elements. The development of a model in the time domain allows to consider nonlinear effects. Additionally temperature effects are taken into account based on the WLF-transformation. Adhesion forces originate from molecular bindings between the contact partners. This effect is simulated by applying a modified model of Achenbach on real surfaces. The temperature distribution within the friction contact region is investigated experimentally as well. Furthermore global stick-slip vibrations of a rubber block element are investigated using a global contact model. Numerical results are compared with experiments performed on a tribometer test rig.

Energy harvesting with piezoelectric Elements - Twiefel, Jens; Hemsel, Tobias; Kauczor, Christopher (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model-based design of piezoelectric energy harvesting systems
In the design process of energy harvesting systems based on piezoelectric elements, achievable energy output is the most interesting factor. To estimate this amount a priori manufacturing of prototypes a mathematical model is very helpful. Within this contribution we will introduce a model based on electro-mechanical circuit theory. Its parameters are identified by measurements and the model is validated by comparison to experimental results. The model is designed to support the development-engineer in the dimensioning of energy harvesting units to specific application demands. Two main challenges in device design are investigated with the mathematical model: influence of the ambient excitation frequency, and influence of the load impedance. Typically, the equivalent model approach delivers models for piezoelectric elements that are driven in resonance by electrical excitation. In the case of energy harvesting the piezoelectric elements are excited mechanically and most often non-resonant. Thus, we first set up a mechanical equivalent model for base excited systems. In first approximation it represents an energy harvesting unit around one resonance frequency. The model is expandable for a wider frequency range using the superpositioning of multiple circuits. From the viewpoint of optimum energy transformation between mechanical and electrical energy it is favorable to drive piezoelectric elements at resonance or anti-resonance. Thus, an energy harvesting system should be tuned to the excitation frequency.

Non-resonant piezoelectric motors driven in audible frequency range - Wilmanns, S; Nakamura, K; Mracek, Maik; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectrics in dental tools - Zhou, W; Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Analysis of the Forced Vibration of Two Bolted Half-Pipes with Extended Friction Contacts - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
The present paper deals with the forced vibration analysis of a test structure. The test structure consists of two parts, an upper and a lower half pipe, joint in two bolted flanges which represent the extended friction contacts. Depending on the clamping loads different normal pressure distributions can be established in the contact interfaces. Since the test structure is loaded with a harmonic external force relative displacements occur in the contact interface. This leads to microslip effects affecting the dynamic behaviour. The experimental validation of the calculation method accounting for these effects is shown by comparing measured and calculated frequency response functions (FRF). (Â{©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Modellgestützte Analyse piezoelektrischer Transformatoren - Hemsel, Tobias (Mechatronik 2005 Innovative Produktentwicklung)

Linear ultrasonic motors based on coupling of longitudinal vibrations - Hemsel, Tobias; Mracek, Maik; Twiefel, Jens; Vasiljev, Piotr; Wallaschek, Jörg (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

Unkontrollierbare Bewegungen ebener Mechanismen mit Gelenkspiel - Hofmeister, Adolf; Sextro, Walter; Röschel, Otto (PAMM)
In dieser Arbeit wird ein analytisches Berechnungsverfahren vorgestellt, mit dem der gesamte Positions- und Orientierungsraum (ErrorWorkspace) ebener Mechanismen mit spielbehafteten Gelenken kinematisch beschrieben bzw. dargestellt werden kann. Für die Berechnung wird der gesamte Positions- und Orientierungsraum im Kinematischen Bildraum dargestellt, wobei auf besondere Merkmale eingegangen wird. Der ErrorWorkspace, der mit Hilfe des Berechnungsverfahren bestimmt wird, wird an einem Koppelgetriebe, an einem Filmgreifergetriebe und an einem Double-rocker four-bar mechanism mit Kurbelantrieb dargestellt und analysiert. ({©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Parallel Operation of Ultrasonic Linear Motors - Mracek, Maik; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

Teaching Mechatronics to a Mixed Audience from Industry and University - Twiefel, Jens; Hemsel, Tobias; Kauczor, Christopher; Wallaschek, Jörg (6th International Workshop on Research and Education in Mechatronics)

Analysis of the Forced Vibration of Two Bolted Half-Pipes with Extended Friction Contacts - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
The present paper deals with the forced vibration analysis of a test structure. The test structure consists of two parts, an upper and a lower half pipe, joint in two bolted flanges which represent the extended friction contacts. Depending on the clamping loads different normal pressure distributions can be established in the contact interfaces. Since the test structure is loaded with a harmonic external force relative displacements occur in the contact interface. This leads to microslip effects affecting the dynamic behaviour. The experimental validation of the calculation method accounting for these effects is shown by comparing measured and calculated frequency response functions (FRF). (Â{©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

A novel approach for high power ultrasonic linear motors - Hemsel, Tobias; Mracek, Maik; Wallaschek, Jörg; Vasiljev, Piotr (Ultrasonics Symposium, 2004 IEEE)
Several positioning tasks demand translatory drive instead of rotary motion. To achieve drives that are capable e.g. to drive the sunroof of a car or to lift a car's window, multiple miniaturized motors can be combined. But in this case many other questions arise: the electromechanical behavior of the individual motors differs slightly, the motor characteristics are strongly dependent on the driving parameters and the driven load, many applications need some extra power for special cases like overcoming higher forces periodically. Thus, the bundle of motors has to act well organized and controlled to get an optimized drive that is not oversized and costly.
Keywords: drives; electromechanical effects; linear motors; ultrasonic motors; car sunroof; car window; electromechanical behavior; high power ultrasonic linear motors; multiple miniaturized motors; positioning tasks; translatory drive; Costs; Electromagnetic forces; Frequency; Laboratories; Manufacturing; Mechatronics; Micromotors; Ultrasonic imaging; Vibrations; Voltage

Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Design criteria for piezoelectric transformers - Littmann, Walter; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics)

Self configuration of miniature ultrasonic linear motors - Mracek, Maik; Wallaschek, Jörg; Hemsel, Tobias (Proceedings of the 18th International Congress on Acoustics)

Asymmetrical Underplatform Dampers in Gas Turbine Bladings: Theory and Application - Panning, Lars; Popp, Karl; Sextro, Walter; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
During operation, the rotating blades of a gas turbine are subjected to centrifugal forces as well as fluctuating gas forces, resulting in blade vibrations. In addition to material damping, aerodynamical and blade root damping, underplatform dampers are widely used to increase the amount of damping and to decrease blade vibration amplitudes. The friction forces generated by the relative displacements between the underplatform damper and the blade platforms provide a significant amount of energy dissipation. In practice, a number of different underplatform damper designs are applied. Basically, these are wedge dampers with flat contact areas, cylindrical dampers with curved surfaces or asymmetrical dampers with both flat contact surfaces on one side and curved contact surfaces on the other. The latter damper type combines the advantages of both the wedge and the cylindrical damper by preventing the damper from pure rolling on the one hand as it has been observed for cylindrical dampers and on the other hand, avoiding a diverged plane area contact in case of a wedge damper, causing a damper lift-off. This paper will focus on the investigation of cylindrical and asymmetrical underplatform dampers. A comparison between measurements of rotating assemblies in Siemens PG gas turbines (V84.2, V64.3A and V94.3A(2)) under test and real operating conditions with cylindrical and asymmetrical underplatform dampers and the predictions of the developed theoretical model are presented. Special attention is paid to the frequency shift due to the application of an underplatform damper, since in particular for stationary gas turbines, in addition to the amplitude reduction, the accurate prediction of the resonance frequency is of major interest. Copyright {©} 2004 by ASME
Keywords: Dampers; Gas turbines

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Model-based Diagnosis for Sandwiched Ultrasonic Transducers - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 18th International Congress on Acoustics, ICA)

Systematic mistuning of bladed disk assemblies with friction contacts - Götting, Florian; Sextro, Walter; Panning, Lars; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)
In turbomachinery, friction contacts are widely used to reduce dynamic stresses in turbine blades in order to avoid expensive damages. As a result of energy dissipation in the friction contacts the blade vibration amplitudes are reduced. In case of so-called friction dampers, which are pressed on the platforms of the blades by centrifugal forces, the damping effect can be optimized by varying the damper mass. This optimization can be done by means of a simulation model applying the so-called component mode synthesis and the Harmonic Balance Method to reduce computation time. It is based on the modal description of each substructure. In a real turbine or compressor blading great differences in the magnitude of the individual blade amplitudes occur caused by unavoidable mistuning of all system parameters like contact parameters and natural frequencies of the blades. It may happen that most of the blades experience only small stresses whereas a few blades experience critical stresses. Therefore, it is necessary to consider mistuning for all system parameters to simulate the forced response of bladed disk assemblies with friction contacts. For a mistuned bladed disk the complete system has to be modeled to calculate the dynamic response. In practice, usually the standard deviations instead of the distributions of the system parameters are known. Therefore, Monte-Carlo simulations are necessary to calculate the forced response of the blades for given mean values and standard deviations of the system parameters. To reduce the computational time, an approximate method has been developed and extended for small and moderate standard deviations of the system parameters to calculate the distribution and the envelopes of the frequency response functions for statistically varying system parameters, in the following called statistical mistuning. The approximate method is based on a sensitivity analysis and the assumption of a Weibull distribution of the vibration amplitudes of the blades. Both, the approximate method and the assumption of a Weibull distribution of the vibration amplitudes are validated by Monte-Carlo simulations. By these investigations the influence of different arrangements of the system parameters for given mean values and standard deviations of the vibration amplitudes of the blades can be determined, too. For the present investigations only a small influence of the arrangement of blades with respect to their natural frequencies has been observed. On the other hand, an intentional mistuning of the damper masses and the natural frequencies of the blades in a systematic way, in the following called systematic mistuning, can be investigated to reduce the amplitudes of the system. The simulation results of a systematic mistuning has been validated by a test rig with a rotating bladed disk assembly with friction dampers. The investigations show a good agreement between the simulations and the measurements but only a slight decrease of the maximum amplitudes in case of a systematic mistuning. Copyright {©} 2004 by ASME
Keywords: Friction; Disks

Linear piezoelectric motors and their application - Hemsel, Tobias (Proceedings of the First International Conference on Ultrasonic Motors and Actuators (IWOUMA))

Schwingungsverhalten von verstimmten Beschaufelungen mit Reibelementen - Götting, Florian; Sextro, Walter; Panning, Lars; Popp, Karl (Schwingungen in rotierenden Maschinen VI SIRM, Referate der Tagung in Darmstadt)

Erzwungene Schwingungen von elastischen Mehrkörpersystemen mit Reibkontakten - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
Im Folgenden wird eine Berechnungsmethode vorgestellt, die es erlaubt, das räumliche Schwingungsverhalten eines elastischen Mehrkörpersystems (EMKS) mit Reibkontakten in rechenzeit- und speicherplatzsparender Form zu analysieren. Der von trockener Reibung und Mikroschlupf geprägte, nichtlineare Dämpfungsmechanismus in den Reibkontakten eines EMKS wird dabei realitätsnahe abgebildet. Die Plausibilität der mit der Methode gewonnenen Berechnungsergebnisse wird beispielhaft an einem einfachen EMKS, einem in Längsrichtung geteilten, einseitig eingespannten Balken gezeigt. Für den geteilten Balken werden die Frequenzgänge des Torsionswinkels um die Längsachse und der Auslenkung um die biegeweiche Achse berechnet.

Modelling and Analysis of Piezoelectric Transformers - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 5th International Congress of Intelligent Materials (ICIM))

Load-adaptive phase-controller for resonant driven piezoelectric devices - Littmann, Walter; Hemsel, Tobias; Kauczor, Christopher; Wallaschek, Jörg; Sinha, W (Proceedings of World Congress Ultrasonics)

Design of Friction Dampers for Mistuned Bladed Disks - Panning, Lars; Sextro, Walter; Popp, Karl (PAMM)
Friction damping devices such as underplatform dampers are widely used in turbomachinery applications to reduce blade vibration amplitudes. In this paper, a model is presented briefly to calculate the forced response of mistuned bladed systems with friction dampers. Some results will give an insight in the vibrational behavior of frictionally damped bladed disks and how the damping gain is affected by the damper properties.

Spatial dynamics of tuned and mistuned bladed disks with cylindrical and wedge-shaped friction dampers - Panning, Lars; Sextro, Walter; Popp, Karl (International Journal of Rotating Machinery)

Vibration Damping by Friction Forces -Theory and Applications - Popp, Karl; Panning, Lars; Sextro, Walter (Journal of Vibration and Control)

Optimierung des Schwingungsverhaltens elastischer Strukturen mit Reibfugen am Beispiel von Turbomaschinenschaufeln - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

On forced vibration of shrouded turbine blades - Szwedowicz, J; Sextro, Walter; Visser, R; Masserey, P.A (ASME Turbo Expo 2003, collocated with the 2003 International Joint Power Generation Conference)
Numerical predictions of the forced vibration of a disc assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disc assembly, numerical static, free and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a non-linear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0--30 deg) between the circumferential direction and the normal vector to the contact surface. Copyright {©} 2003 by ASME
Keywords: Turbine blades; Vibration

Piezoelectric transformers - state of the art and development trends - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (Ultrasonics Symposium, 2002. Proceedings. 2002 IEEE)
Piezoelectric transformers are well known since the publication of some patent applications at the end of the 1950s. But until today their only business use lies in the field of backlighting systems for LCDs. Due to key features as light-weight, flatness, high step-up at low volume and high efficiency piezoelectric transformers should be usable in a much broader range of applications. This contribution returns to mind their operating principle, shows how to model and to develop such devices as well as give some aspects for development trends that will lead to further applications.
Keywords: piezoelectric devices; reviews; transformers; backlighting systems; flatness; high efficiency piezoelectric transformers; high step-up; light-weight; low volume; operating principle; piezoelectric transformers; Circuits; Costs; Electromagnetic devices; Electromagnetic fields; Mechanical energy; Piezoelectric materials; Power electronics; Switching frequency; Transformers; Vibrations

Piezoelektrische Transformatoren - Bauformen und Modellierung - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (47. Internationales Wissenschaftliches Kolloquium)

Optimization of the Contact Geometry between Turbine Blades and Underplatform Dampers with respect to Friction Damping - Panning, Lars; Sextro, Walter; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)

Spatial dynamics of tuned and mistuned bladed disks with cylindrical and wedge-shaped friction dampers - Panning, Lars; Sextro, Walter; Popp, Karl (Proceedings of the 9th International Symposium on Transport Phenomena and Dynamics of Rotating Machinery, ISROMAC)

Fast Calculation of the Statistics of the Forced Response of Mistuned Bladed Disk Assemblies with Friction Contacts - Sextro, Walter; Panning, Lars; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)

Optimierung des Schwingungsverhaltens elastischer Strukturen mit Reibfugen - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW) - lnformationstagung Turbinen)

Schwingungsanalyse verstimmter Schaufelkränze mit Reibelementen - Panning, Lars; Sextro, Walter; Popp, Karl (Schwingungen in rotierenden Maschinen VI SIRM, Referate der Tagung in Wien)

Heat and Wear Generation for Rolling Contacts - Sextro, Walter (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Development and Experimental Validation of a Point Contact Model for Dynamical Problems with Friction - Sextro, Walter (ASME Design Engineering Technical Conferences)

Localization in Nonlinear Mistuned Systems with Cyclic Symmetry - Sextro, Walter; Popp, Karl; Krzyzynski, Tomasz (Nonlinear Dynamics)
In forced systems with cyclic symmetry localization can occur due toparameter uncertainties. Often, Monte-Carlo simulations are used to findregions, where the system response is sensitive to parameteruncertainties. These simulations require a large computation time.Therefore, an approximate method to calculate the envelopes of thefrequency response functions is developed in this paper. An example of anonlinear system with cyclic symmetry is a bladed disk assembly withfriction dampers. Friction dampers can be installed underneath the bladeplatforms of turbine blades. Due to dry friction and the relative motionbetween blades and dampers, energy is dissipated, which results in areduction of blade vibration amplitudes. By optimizing the mass of thefriction dampers, the best damping effects are obtained, which lead toan increase in the reliability of the turbine. In this paper, thecalculated response of a mistuned bladed disk assembly with frictiondampers is discussed. An approximate method is developed to calculatethe envelopes of the corresponding frequency response function forstatistically varying eigenfrequencies of the blades. Regions wherelocalization can occur with a high probability, are calculated by thismethod.
Keywords: bladed disk assembly; mistuning; sensitivity; localization

Piezoelektrische lineare Schwingungsantriebe - Wallaschek, Jörg; Hemsel, Tobias (Special Antriebstechnik)

Untersuchung und Weiterentwicklung linearer piezoelektrischer Schwingungsantriebe - Hemsel, Tobias

Survey of the present state of the art of piezoelectric linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
Piezoelectric ultrasonic motors have been investigated for several years and have already found their first practical applications. Their key feature is that they are able to produce a high thrust force related to their volume. Beside rotary drives like the travelling wave motor, linear drives have also been developed, but only a few are presently commercially available. In the present paper, we first describe the state of the art of linear piezoelectric motors. The motors are characterized with respect to their no-load velocity, maximum thrust force, efficiency and other technical properties. In the second part, we present a new motor, which is judged to be capable of surpassing the characteristics of other piezoelectric motors because of its unique design which allows the piezoelectric drive elements to be pre-stressed in the direction of their polarization. The piezoelectric elements convert energy using the longitudinal d33 effect which allows an improved reliability, large vibration amplitudes and excellent piezoelectric coupling. Energy loss by vibration damping is minimized, and the efficiency can be improved significantly. Experimental results show that the motor characteristics can be optimized for a particular task by choosing the appropriate operating parameters such as exciting voltage, exciting frequency and normal force.
Keywords: Linear motor

State of the art and development trends of ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics Symposium, 2000 IEEE)
Ultrasonic linear motors have now been investigated for several years. Their key features are high thrust forces related to their volume and good position-accuracy. This contribution consists of two main parts. In the first part we describe the state-of-the-art of linear piezoelectric motors. Characteristics like no-load velocity, maximum thrust force and other technical properties of commercially available devices will be reported as well as those of prototypes. In the second part we report an ongoing research and development project aiming at a linear piezoelectric motor, which is capable of surpassing some of the shortcomings of other piezoelectric motors
Keywords: linear motors; ultrasonic motors; linear piezoelectric motor; maximum thrust force; no-load velocity; ultrasonic linear motor; Electromagnetic devices; Electromagnetic fields; Frequency; Friction; Gears; Materials science and technology; Piezoelectric materials; Research and development; Vibrations; Wheels

Piezoelectic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Tagungsband der ACTUATOR)

Stand der Technik und Entwicklungsperspektiven linearer piezoelektrischer Schwingungsantriebe - Hemsel, Tobias; Wallaschek, Jörg
Piezoelektrische Schwingungsantriebe sind Kleinmotoren, deren Funktionsprinzip darin besteht, dass elektrische Energie mit Hilfe von Piezokeramiken in mechanische Schwingungsenergie gewandelt und diese dann durch hochfrequente Kontaktvorgänge auf den anzutreibenden Teil übertragen wird. Der Stand der Technik auf dem Gebiet piezoelektrischer Linearantriebe zeigt, dass viele piezoelektrische Linearantriebe bereits zufriedenstellende Leistungsmerkmale aufweisen. Gleichzeitig ist zu erwarten, dass die Leistungen dieser Antriebe noch deutlich verbessert werden können. Ein Ansatz, insbesondere den Wirkungsgrad und die mechanische Leistung zu erhöhen, wird anhand eines Motors aufgezeigt, der am Heinz Nixdorf Institut entwickelt wurde. Eine Übersicht der in ausgewählten Einsatzgebieten geforderten Leistungsdaten führt auf Entwicklungsziele für bestehende und neuartige piezoelektrische Linearantriebe.

On some regularities in dynamic response of cyclic periodic structures - Krzyzynski, Tomasz; Popp, Karl; Sextro, Walter (Chaos, Solitons & Fractals)
The paper deals with cyclic periodic structures modelling bladed disk assemblies of blades with friction elements for vibration damping. These elements placed between adjacent blades reduce the vibration amplitudes by means of dry friction resulting from centrifugal forces acting on the elements and relative displacements of the blades. However, the application of these friction elements results in an additional dynamical coupling which together with mistuning of some system parameters (e.g., blade eigenfrequency or contact parameters) may cause localization of vibration. In the present paper a linear approximation of such a system is investigated. The structure composed of cyclic periodic cells modelled each as a clamped-free beam interacting with each other by means of viscoelastic elements of complex stiffness is applied for dynamic system analysis. In case of free vibrations as well as in case of steady-state dynamic response to a harmonic pressure field, a perfect periodic structure and the structures with periodically mistuned parameters (blade eigenfrequencies and contact parameters) are studied. Some regularities in the dynamic response of the systems with mistuning have been noticed. Despite the fact that only a linear approximation has been used, the results and conclusions can be applied for models which describe the blade interaction in a nonlinear way.

Optimization of Interblade Friction Damper - Panning, Lars; Sextro, Walter; Popp, Karl (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)
the vibration amplitudes of bladed disk assemblies can be reduced significantly by means of friction damping devices such as shrouds, damping wires and interblade Friction dampers. in practice, interblade Friction dampers are applied in rotating arrangements with various geometries showing curved or flat surfaces like so-called wedge-shaped dampers. this paper is focusing on a computation method to predict the dynamical behaviour of turbine blades with Friction dampers including both, curved and wedge-shaped dampers with hertzian and non-herutian contact conditions, respectively. the presented computation method uses a 3d contact model to calculate the contact forces, including normal and tangential stiffnesses, roughness and microslip effects. the relative displacements in the contact area can be expressed by means of 6 dof of the blade platforms and 6 rigid body dof of the damper including translational and rotational displacements. the relative displacement of the Friction damper with respect to the adjacent blades can be derived from the contact kinematics of the blade-damper-blade system and the equations of motion of the Friction damper. thus, the model can be applied to investigate spatial motions of the bladed disk assembly including bending and torsional vibrations. a comparison of different Friction damper designs with respect to an optimal damper geometry and damper mass is presented. the advantages and disadvantages of each design will be discussed. experimental results are shown to validate the developed computation method.

The Calculation of the Forced Response of Shrouded Blades with Friction Contacts and Its Experimental Verification - Sextro, Walter (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Experimental verification of a non-Hertzian contact model - Sextro, Walter (International conference on computational methods in contact mechanics)

Forced Vibration of Elastic Structures with Friction Contacts - Sextro, Walter (ASME Design Engineering Technical Conferences)

Ein ebenes Reibkontaktmodell zur Berechnung von Schaufelschwingungen mit Reibelementen - Sextro, Walter; Popp, Karl (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

Modellierung piezoelektrischer Stapel- und Vielschichtaktoren für dynamischen Betrieb - Hemsel, Tobias; Krome, Jürgen; Littmann, Walter; Wallaschek, Jörg (Proceedings 2. Polnisch-Deutscher Workshop "Werkzeuge der Mechatronik")

A piezoelectric linear vibration drive for high driving forces - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of VIBROENGINEERING)

Vibrational Behaviour of Tuned and Detuned Bladed Disks with Friction Dampers - Sextro, Walter; Popp, Karl; Wolter, I (International Congress on Combustion Engines, Proceedings of the 22nd CIMAC)

Three-Dimensional Vibration of Bladed Disk Assemblies with Friction Dampers - Sextro, Walter; Popp, Karl; Wolter, I (The 7th International Symposium on Transport Phenomena and Dynamics of Rotating Machinery, Proceedings of ISROMAC-7)

Schwingungsprüfstand zur vollautomatischen Messung von Ultraschallschwingungen in piezoelektrischen Antrieben - Goldschmidt, Stefan; Hemsel, Tobias; Krome, Jürgen; Storck, Heiner; Wallaschek, Jörg (Tagungsband zum 4. Laser Vibrometer Seminar der Polytec GmbH)

Ultrasonic motors for linear positioning tasks in automobiles - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 30th International Symposium on Automotive Technology & Automation (ISATA))
Piezoelectric ultrasonic motors are a new kind of actuators that produce high driving-forces related to their volume. Beside rotary drives like the travelling wave motor many linear drives have been developed and are already commercially available today. These motors can provide static holding-forces and driving-forces of up to 30 N at velocities of up to 220 mm/s. These operational characteristics, which are expected to be improved continuously, make these devices attractive as direct-drives for sliding roofs or windows in automobiles. In this contribution a short outline of the present state-of-the-art of linear ultrasonic motors is given. Different operating principles are compared with respect to the potential driving-force and power. Finally the working-principle of a newly developed motor, which uses the piezoelectric d33-effect, is explained in detail. Theoretical and experimental results show that this motor is capable of achieving high driving-force and rated output-power

Piezoelectric ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (EUROMECH, European Mechanics Colloquium "Synthesis of Mechatronic Sytems")

Schwingungsverhalten von verstimmten Beschaufelungen mit Reibelementen - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Schwingungsverhalten von Schaufelkränzen mit Reibelementen bei Frequenzverstimmung - Sextro, Walter (VDI-Reihe)

Improved reliability of bladed disks due to friction dampers - Sextro, Walter; Popp, Karl; Wolter, Ivo (The 1997 International Gas Turbine & Aeroengine Congress & Exposition)

Schwingungsverhalten eines Schaufelkranzes mit Reibelementen bei Frequenzverstimmung - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) - lnformationstagung Turbinen)

Dynamical Behaviour of a Bladed Disk with Friction Dampers - Popp, Karl; Sextro, Walter (The 2nd European Nonlinear Oscillation Conference - Proceedings of EUROMECH)